2022
DOI: 10.3390/cells12010089
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio fairfieldensis-Derived Outer Membrane Vesicles Damage Epithelial Barrier and Induce Inflammation and Pyroptosis in Macrophages

Abstract: Sulfate-reducing bacteria Desulfovibrio fairfieldensis is an opportunistic pathogen that widely exists in the human intestine and can cause severe infectious diseases. However, the mechanisms contributing to its pathogenesis remain of great interest. In this study, we aim to investigate the outer membrane vesicles (OMVs) secreted by D. fairfieldensis and their pathogenic effect. The OMVs separated by ultracentrifugation were spherical and displayed a characteristic bilayer lipid structure observed by transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Desulfovibrio_fairfieldensis is an opportunistic pathogen that is widespread in the human gut and can cause serious infectious diseases. 59 Interestingly, no detectable changes in Lactobacillus_taiwanensis were seen in any of the four immunized groups at 16 weeks compared to 2 weeks post-immunization, while two probiotics, Lactobacillus_reuteri and Lactobacillus_ intestinalis, increased significantly during that time. Meanwhile, the unclassified_Lachnospiraceae_NK4A136_ group bacteria in the rEg.P29 T + CpG group were significantly elevated, which was highly consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Desulfovibrio_fairfieldensis is an opportunistic pathogen that is widespread in the human gut and can cause serious infectious diseases. 59 Interestingly, no detectable changes in Lactobacillus_taiwanensis were seen in any of the four immunized groups at 16 weeks compared to 2 weeks post-immunization, while two probiotics, Lactobacillus_reuteri and Lactobacillus_ intestinalis, increased significantly during that time. Meanwhile, the unclassified_Lachnospiraceae_NK4A136_ group bacteria in the rEg.P29 T + CpG group were significantly elevated, which was highly consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…This may be attributed to the fact that vaccine immunization triggers a strong immune response in mice, leading to a decline in some of the flora that have been implicated in the inflammatory response. Desulfovibrio_fairfieldensis is an opportunistic pathogen that is widespread in the human gut and can cause serious infectious diseases 59 . Interestingly, no detectable changes in Lactobacillus_taiwanensis were seen in any of the four immunized groups at 16 weeks compared to 2 weeks post‐immunization, while two probiotics, Lactobacillus_reuteri and Lactobacillus_intestinalis, increased significantly during that time.…”
Section: Discussionmentioning
confidence: 96%
“…Our study also showed that DSV may promote the growth of D. fairfieldensis , which may be an invasive and pathogenic genus and can cause severe bacteremia 72 . D. fairfieldensis -derived outer membrane vesicles are found to damage the intestinal epithelial barrier and activate intrinsic inflammation 73 . The relationship between D. desulfuricans with other Desulfovibrio species are also worth investigating in the future to evaluate their different impacts on liver health.…”
Section: Discussionmentioning
confidence: 99%
“…It may contribute to regulating the cervical microenvironment and facilitating normal cervical maturation. Desulfovibrio fairfieldensis [ 49 ] is associated with inflammatory bowel disease and may impact cervical maturation progression through inflammation. Surprisingly, its abundance is lower in the immature cervix group, necessitating further investigation into the underlying reasons.…”
Section: Discussionmentioning
confidence: 99%